Humans of New York - Stanton, Brandon (St. Martin's Press, 2013)
"In the summer of 2010, photographer Brandon Stanton set out on an ambitious project: to single-handedly create a photographic census of New York City. Armed with his camera, he began crisscrossing the city, covering thousands of miles on foot, all in his attempt to capture ordinary New Yorkers in the most extraordinary of moments"--